Chains of Love and Beauty : The Diary of Michael Field - Dever, Carolyn (Book collections on Project MUSE., 2022)
""Michael Field" was the pseudonym of two women writing as a male author: Katharine Bradley and Edith Cooper, who were aunt and niece, and a devoted couple for three decades that spanned the late nineteenth and the early twentieth centuries. While much has been written about the Fields' many volumes of poetry and plays, and about their strange and complicated life, this book is the first to focus on their diary, which they kept for twenty-five years and viewed as an "unpublished manuscript" called Works and Days. In this book, Dever argues that Works and Days represents one of the great experimental prose narratives of the transitional period between Victorian and modernist literature. Through the co-written diary, which fills twenty-nine volumes and about 9,500 pages, the women envisioned a life beyond the tight horizons of one home and one family, and portrayed new forms of women's intimacy at the dawn of the twentieth century. Dever focuses on five pivotal years in the life of Bradley and Cooper as reflected in the diary: the death of Cooper's mother; a year of personal and professional humiliation; the death of Cooper's father; the women's establishment of their home together; and the event they experience as a devastating loss, the death of their dog Whym Chow. In this examination of the Fields' most personal writing, Dever establishes their unlikely role as a bridge between the Victorians and the experiments of modernism to come"--